A Core–Shell Nanoplatform for Synergistic Enhanced Sonodynamic Therapy of Hypoxic Tumor via Cascaded Strategy. Issue 22 (10th October 2018) - Wang, Lei; Niu, Mengya; Zheng, Cuixia; Zhao, Hongjuan; Niu, Xiuxiu; Li, Li; Hu, Yujie; Zhang, Yingjie; Shi, Jinjin; Zhang, Zhenzhong
Abstract: Sonodynamic therapy (SDT) always causes tumor hypoxia aggravation which can induce malignant cell proliferation and drug resistance. To overcome these disadvantages, a cascaded drug delivery system (Lipo/HMME/ACF@MnO2 ‐AS1411) is constructed for synergistic enhanced sonodynamic therapy. First, hematoporphyrin monomethyl ether (HMME) and acriflavine (ACF) are encapsulated in the lipid layers and the inner aqueous cores of the liposomes, respectively. Then the ultrathin manganese dioxide (MnO2 ) nanosheets are coated on the surface of the liposomes by using KMnO4 and polyethylene glycol through "one step reduction and modification" method. Furthermore, the nanoparticles are decorated with tumor‐targeting AS1411 aptamer through the phosphate groups on the DNA strand which can bind to Mn sites to obtain Lipo/HMME/ACF@MnO2 ‐AS1411 delivery system. Herein, HMME can act as a sonosensitizer, and ACF is used to prevent the formation of HIF‐1α/HIF‐1β dimerization to overcome the negative effects after SDT. The Lipo/HMME/ACF@MnO2 ‐AS1411 delivery system has multiple functions, including codelivery of HMME and ACF, pH/glutathione/ultrasound triple responses, synergistic cascaded enhancement of SDT, precise tumor‐targeting, and magnetic resonance imaging. The in vitro and in vivo results suggest that the Lipo/HMME/ACF@MnO2 ‐AS1411 delivery system is a promising core–shell nanoplatform for synergistic enhancement of sonodynamic therapy, which can provide a new approach in the related research fields. Abstract : Hematoporphyrin monomethyl ether (HMME) and acriflavine (ACF) coloaded and AS1411 aptamer conjugated core–shell structured drug delivery system (Lipo/HMME/ACF@MnO2 ‐AS1411) is a potent therapeutic nanoplatform for dual‐drug delivery, synergistic cascaded enhancement of sonodynamic therapy, pH/glutathione/ultrasound triple sensitive controlled release, precise tumor‐targeting, and magnetic resonance imaging, which is beneficial for integrative cancer therapies.